Skunkdog - Jenkins, Emily, frey50; Pratt, Pierre (New York : Farrar, Straus and Giroux, 2008)
Dumpling, a lonely dog with no sense of smell, moves with his family to the country and makes a new friend who takes some getting used to.
"Frances Foster Books."
Keywords: Friendship; Dogs; Skunks